Captain Underpants and the attack of the talking toilets : another epic novel - Pilkey, Dav, 1966- (New York : Blue Sky Press, 1999)
While sitting in detention, George and Harold accidentally create an army of evil talking toilets, and Principal Krupp's alter ego, Captain Underpants, has to save the world from it.
School Library Journal, June 1999.
Publisher's Weekly, February 1999.
Booklist, May 1999.
New York Times, June 1999.
Bulletin (Center for Children's books), May 1999.
Library Talk, September 1999.
Keywords: Captain Underpants (Fictitious character) -- Fiction; Schools -- Fiction; School principals -- Fiction; Heroes -- Fiction; Toilets -- Fiction; Cartoons and comics -- Fiction; Humorous stories; Captain Underpants (Fictional character) -- Fiction; School stories; School superintendents and principals -- Fiction; Heroes and heroines -- Fiction; Toilets -- Fiction; Humorous fiction; School principals -- Fiction; Heroes -- Fiction; Cartoons and comics -- Fiction; Humorous stories; Schools -- Fiction